2020
DOI: 10.1038/s10038-020-00844-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell genomics to understand disease pathogenesis

Abstract: Cells are minimal functional units in biological phenomena, and therefore single-cell analysis is needed to understand the molecular behavior leading to cellular function in organisms. In addition, omics analysis technology can be used to identify essential molecular mechanisms in an unbiased manner. Recently, single-cell genomics has unveiled hidden molecular systems leading to disease pathogenesis in patients. In this review, I summarize the recent advances in single-cell genomics for the understanding of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 113 publications
0
19
0
Order By: Relevance
“…However, our data suggest that the MRSD model may be readily applicable to RNA-seq generated using alternative methodologies, such as increased read length, with only minor variations in model performance (Figure S6). As other technologies, such as long-read, [40][41][42] single-cell, 43,44 and spatially resolved RNA-seq, [45][46][47][48] become more prevalent in a clinical setting,…”
Section: Figure 4 Expanding Control Datasets and Enforcing Read Count Thresholds Improves Filtering Power When Analyzing Mis-splicing Evementioning
confidence: 99%
“…However, our data suggest that the MRSD model may be readily applicable to RNA-seq generated using alternative methodologies, such as increased read length, with only minor variations in model performance (Figure S6). As other technologies, such as long-read, [40][41][42] single-cell, 43,44 and spatially resolved RNA-seq, [45][46][47][48] become more prevalent in a clinical setting,…”
Section: Figure 4 Expanding Control Datasets and Enforcing Read Count Thresholds Improves Filtering Power When Analyzing Mis-splicing Evementioning
confidence: 99%
“…This experimental RNAseq approach currently remains widespread (3,10,(13)(14)(15); however, our model may be readily applicable to RNA-seq generated using alternative methodologies, such as increased read length, with only minor variations in model performance ( Supplementary Figure 3). As other technologies, such as long-read (36)(37)(38), singlecell (39,40) and spatially resolved RNA-seq (41)(42)(43)(44), become more prevalent in a clinical setting, appropriate control datasets must be generated to develop corresponding MRSD models. Similarly, recent research has shown noticeable improvements to diagnostic yield for neuromuscular disorders by conducting RNAseq on in vitro myofibrils generated by a fibroblast-to-myofibril transdifferentiation protocol (45).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of budget, current advances of protocols as well as standardization of bioinformatics pipelines warrants the SCS approach as a realistic option for clinical applications in the near future. Importantly, conventional single-cell RNA-seq analysis may not be sufficient for obtaining the information necessary for a deeper understanding of molecular behavior and therefore combined bulk sequencing analysis will be mandatory for a more precise analysis (66).…”
Section: Real-time Single Cell Transcriptome Profile Of the Heart The...mentioning
confidence: 99%